Energy, resources & the environment: Current status - Juhlin, Christopher; Hangx, S.; Ask, M.; Bruckman, V. (Elsevier Ltd, 2014)
© 2014 The Authors. The EGU gathers geoscientists from Europe and the rest of the world, covering all disciplines of geosciences. Geoscientific interdisciplinarity is needed to tackle future challenges. A major challenge regards the provision of adequate and reliable supplies of affordable energy and resources obtained in environmentally sustainable ways, which are essential for economic prosperity, environmental quality and political stability around the world. One goal of the ERE division is to be a leading discussion forum for these subjects. The contributions in this issue present some of the challenges that were presented in the ERE division at the EGU General Assembly in 2014.